Why base-catalyzed isomerization of N-propargyl amides yields mostly allenamides rather than ynamides - Navarro-Vázquez, Armando (Beilstein Journal of Organic Chemistry, 2015)
The base-catalyzed isomerization of N-propargylamides or carbamates may furnish N-allenyl compounds (allenamides/allencarbamates) or further evolve to N-alkynyl compounds (ynamides or yncarbamates). The particular fate of this reaction varies from experiment to experiment and there is no clear rule for predicting the reaction outcome for a particular structure. With the support of ab initio and DFT computations, this work shows that observed results can be explained by assuming an exchange equilibrium between energetically close N-propargyl, allenyl and N-alkynyl forms and that the reaction outcome correlates to a particular equilibrium mixture. Due to the very small energy gap between the N-allenyl and N-alkynyl forms, small structural changes may easily alter the equilibrium position, explaining the variety of observed experimental results. Based on CBS-QB3 computations, the ωB97 functional provided reasonably accurate isomerization energies and could successfully predict the experimentally observed behavior for several examples from the literature.
Keywords: allenamide; DFT; isomerization; ynamide